Ezetimibe use and mortality after myocardial infarction : A nationwide cohort study - Kytö, Ville; Tornio, Aleksi (Elsevier, 2025)
Background The inhibition of intestinal cholesterol absorption by ezetimibe improves outcomes after myocardial infarction (MI), yet real-world data on ezetimibe is scarce. We studied the usage of ezetimibe and association with outcome after MI. Methods Consecutive MI patients in Finland (2010-2018) were retrospectively studied (N = 57,505; 65% men; mean age 69 years). The study data were collected from national registries. The median follow-up was 4.5 (IQR 2.8-7.1) years. Between-group differences were adjusted for using multivariable regression. Ezetimibe use was studied with competing risk analyses. Results The cumulative incidence of ezetimibe use was 3.7% at 90 days, 13.4% at 5 years, and 19.8% at 10 years. Younger age was one of the strongest predictors of ezetimibe use (adj.sHR 6.67; CI 5.88-7.69 for patients aged <60 vs ≥80 years). Women were more likely to use ezetimibe during follow-up than men. The average proportion of patients using ezetimibe during follow-up was 6.8%. (11.7% at 10 years). Ezetimibe was discontinued by 43.6% of patients during follow-up. Patients with early ezetimibe therapy after MI had lower all-cause mortality during follow-up (33.6% vs 45.1%; adj.HR 0.77; CI 0.69-0.86; P<0.0001). Early ezetimibe use was associated with lower mortality irrespective of sex, age, atrial fibrillation, diabetes, heart failure, malignancy, revascularization, or statin use. Ongoing ezetimibe therapy during follow-up was associated with lower mortality in a time-dependent analysis (adj.HR 0.53; CI 0.48-0.59; P<0.0001). Conclusions Ezetimibe is associated with a lower risk of death after MI, yet its therapeutic use is limited, and discontinuation is frequent.